Recycling cooperatives: Problems and challenges for social development - Santos, Richard Apolonio [UNESP]; Deus, Rafael Mattos [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP] (My University, 2018)
Municipal Solid Waste is still a challenging area for the integral municipalities sustainability because it involves economic, environmental and social issues. This paper traces a profile of three recyclable cooperatives in the city of Bauru, SP, Brazil, mapping and identifying the specificities of each one. We identified as challenges: dealing with the low education and knowledge of waste pickers, lack of knowledge of the labor rights and difficulty in finding buyers for recyclable waste.
Cooperativas de reciclagem: Problemáticas e desafios para o desenvolvimento sustentável
Keywords: Environmental management; Recyclable cooperative; Social development; Solid waste